A GC-rich sequence feature in the 3′ UTR directs UPF1-dependent mRNA decay in mammalian cells - Imamachi, Naoto; Salam, Kazi Abdus; Suzuki, Yutaka; Akimitsu, Nobuyoshi (Genome Research, 2017)
Up-frameshift protein 1 (UPF1) is an ATP-dependent RNA helicase that has essential roles in RNA surveillance and in post-transcriptional gene regulation by promoting the degradation of mRNAs. Previous studies revealed that UPF1 is associated with the 3′ untranslated region (UTR) of target mRNAs via as-yet-unknown sequence features. Herein, we aimed to identify characteristic sequence features of UPF1 targets. We identified 246 UPF1 targets by measuring RNA stabilization upon UPF1 depletion and by identifying mRNAs that associate with UPF1. By analyzing RNA footprint data of phosphorylated UPF1 and two CLIP-seq data of UPF1, we found that 3′ UTR but not 5′ UTRs or open reading frames of UPF1 targets have GC-rich motifs embedded in high GC-content regions. Reporter gene experiments revealed that GC-rich motifs in UPF1 targets were indispensable for UPF1-mediated mRNA decay. These findings highlight the important features of UPF1 target 3′ UTRs.